Realization of French Connected Speech: A Comparative Study between Indonesian FLE Students and Native Speakers - Nani Kusrini; Sajarwa Sajarwa; Hayatul Cholsy (Journal of Language and Literature, 2025)
This study aims to explain the realization of French external sandhi, namely liaison, enchaînement, and élision in FLE (French as a Foreign Language) students with Indonesian as their first language (L1), and the factors influencing the realization. To determine the extent of mastery of Indonesian students, this study compared the realization of two groups of Indonesian students with different study hours and the realization of native speakers. This study involved 44 FLE students divided into two groups (27 students in Group I and 17 in Group II) and 11 native speakers. The instrument text for oral reading was compiled considering all these three phenomena theoretically and the students' competence level. It contains sequences of words potentially connected by all three. The data collection technique was carried out by recording the text reading once. The use of PRAAT software supported data analysis. The study results indicate the mastery of Indonesian speakers in élision liaison enchaînement consonantique enchaînement vocalique. The realization level of the students is much lower than that of native speakers. Several factors include the absence of similar phenomena in L1, segmentation ability, use of rhythm, differences in the orthographic systems, and interference, namely the presence of silent consonants and grapheme h, which are not pronounced in French, differences in the transparency of phoneme-grapheme relationship in the two languages and the quality of input.